Significance of CNS 2 cerebrospinal fluid status post‐induction in pediatric and adolescent patients with acute lymphoblastic leukemia. Issue 1 (11th September 2018) - Gurunathan, Arun; Desai, Ami V.; Bailey, L. Charles; Li, Yimei; Choi, John K.; Rheingold, Susan R.
Abstract: Background: At diagnosis, there are prognostic implications of low‐level leukemic blasts (CNS 2) in the cerebrospinal fluid (CSF) of patients with acute lymphoblastic leukemia (ALL). However, the significance of post‐induction CNS 2 results and the impact of equipment on CNS 2 prevalence have not been well studied. Procedure: A single‐institution retrospective cohort study was conducted to analyze the outcome of patients with ≥1 post‐induction CNS 2. A subanalysis compared the proportion of CNS 2 CSF results using 2 different cytocentrifuges; the Shandon Cytospin used from 2005 to 2008 and the Wescor Cytopro used from 2010 to 2014. Results: Over 4500 post‐induction CSF samples were analyzed, of which 59 were CNS 2. In covariate‐adjusted analyses, post‐induction CNS 2 did not significantly increase relapse risk. The proportion of CNS 2 results increased 4.3‐fold in noninfants and 6.3‐fold in infants using the Wescor Cytopro. Cytocentrifuge machine did not affect CNS 3 prevalence. Conclusions: These findings support our current practice of not changing management based on a post‐induction CNS 2 CSF and highlight how equipment changes can significantly influence testing results. More data are needed to analyze relapse by subpopulations, such as those with repeated CNS 2 findings.